2019
DOI: 10.1055/s-0039-1693437
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Blepharoplasty

Abstract: The eyes and periorbital region are central components of facial beauty and harmony, but the periorbital region is also one of the earliest to show signs of aging. Over the past few decades, significant progress has been made in our understanding of the anatomy in this area, as well as the deleterious effects of aging in this region. In turn, surgical philosophy and techniques have evolved to better combat changes in this area to achieve a more youthful, natural appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 110 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…The periorbital region is not only the earliest aging part of the face, but also the most exposed area of the human body, especially during the pandemic due to the use of surgical masks due to viral infection 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The periorbital region is not only the earliest aging part of the face, but also the most exposed area of the human body, especially during the pandemic due to the use of surgical masks due to viral infection 9 …”
Section: Discussionmentioning
confidence: 99%
“…The periorbital region is not only the earliest aging part of the face, but also the most exposed area of the human body, especially during the pandemic due to the use of surgical masks due to viral infection. 9 The increasing demand and popularity of treatment of the periorbital area have been observed among patients, especially in the inferior orbital rim, due to the aging effect resulting in a loss of the suborbicularis oculi fat pads, since hollow eyes give the appearance of tiredness. HA fillers were FDA approved in 2003 and have been preferred by those looking for a quick, temporary, nonsurgical procedure with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…With a deeper understanding of aesthetics, an increasing number of studies on facial proportional aesthetics have been reported. 3 , 4 Plastic surgeons increasingly declare that the upper part of the face should be considered an extended aesthetic unit, and all patients who present for blepharoplasty should undergo an evaluation of their forehead and eyelids. 17 In our study, the complete design of the palpebral crease line was based on the evaluation of patients’ periorbital region ratio.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, a recent cadaveric study of Asian eyelids showed that distinctions in the volume and configuration of upper eyelid fat probably lead to differences in the appearance. 3 Generally speaking, orbital fullness is a symbol of youth, but orbital swelling is undesirable. Excessive orbital fat can even affect the height of the marginal reflex distance (MRD1) when the eyelids are open.…”
Section: Introductionmentioning
confidence: 99%
“…T he upper eyelid is the earliest and most obvious area of aging due to long-term sunlight exposure, thin skin, and frequent muscle activity. 1 In aging, some senile patients experience upper-eyelid depression, ptosis, and higher eyelid crease, which show the appearance of fatigue and block vision, seriously affecting daily life. A sunken upper eyelid refers to a depressed area between the tarsus and supraorbital rim, imparting a tired and aging appearance.…”
mentioning
confidence: 99%